Accountability por resultados na administração pública : estudo de caso de auditorias operacionais realizadas pelo Tribunal de Contas do Estado de Minas Gerais - Couto, Daniel Uchôa Costa (2014)
The Constitution of 1988 (CR/88) assigned to the Courts of Auditors (TCs) an important role in the national accountability system, in view of the accounting, financial, budgetary, operational and patrimonial oversight of public administration. The competency for conducting performance audits (AOPs), innovation brought by CR/88, has provided important tool for operational control by TCs, aimed at examining the performance of agencies or entities or the results of policies or public programs. However, implementation of AOPs requires the referred control agencies face challenges and difficulties, in view of the combination of accountability for results with accountability of regularity, traditionally realized, whose focus refers to the verification of compliance with rules and procedures prearranged with the potential punishment of managers in case of irregularities. This research sought to examine whether the AOPs have been able to move beyond compliance audits, i.e. check which has been the scope and limits of the control exercised by those audits. To do this, were examined the techniques and methods of audit used, as well as the approaches and audits criteria adopted. It has also sought to verify how has being faced challenges in the implementation of AOPs, in the light of the literature, involving: the combination of accountability of regularity with accountability for results, information asymmetry between auditors and auditees, the need for establishment of partnership between them and the implementation of recommendations made by the TC. Furthermore, the use of the information presented in the final report of AOPs by entities involved in the programs audited has been examined. As methodological strategy for data collection, it has been proceeded to the desk review of the final report of the AOPs realized by TCEMG selected and to the application of questionnaires, both at the external and the internal levels of the referred control agency. The results revealed that the AOPs were able to move beyond compliance audits, to produce and present information suitable to contribute to the improvement of the audited public programs and to the improvement of accountability. However, it has been noticed several points indicative of the need for investment and improvements relating to the TC and to the agencies or to the entities subject to such audits. It has also been assessed challenges for the performance of AOPs, notably the resistance of representatives of entities involved in the programs to be submitted to AOP and fears about the possible negative political repercussions of the findings of the audits.